'Men don't do Botox, they do Brotox' – Emerging Configurations of Masculinity in the Marketing of Cosmetic Treatments Online. (April 2021) - Rasmussen, Signe Rom
Abstract : Non-invasive cosmetic treatments are increasingly popular, and the cosmetic skincare industry is currently experiencing growth at a global scale. Men are reported to constitute a growing consumer segment of this emerging market and accordingly, men are being targeted in the marketing of cosmetic skincare clinics (International Society of Aesthetic Plastic Surgery 2018). On clinic websites, content is emerging as "especially for men". This feeds into the contemporary phenomena that men's bodies are increasingly visible through a range of lifestyle industries such as fashion, fitness, tattooing, and grooming (Bordo 1999, Gill et al. 2005, Hakim 2019 ). Men have, in Western culture, traditionally been expected to take on a 'functional, aloof and distanced' relationship to their bodies (Coffey 2016 ). In this article, I explore how masculinity and embodiment are negotiated in the online marketing of men's cosmetic treatments, as the male body is increasingly imagined as susceptible to cosmetic enhancement. Inspired by the somatechnical framework, I analyse the website marketing of three leading Danish cosmetic skincare clinics: Aglaia-klinikken, N'age, and DermoCosmetic. I argue that masculinity here is negotiated and produced as ambiguous, configuring between emergent and hegemonic forms (Inhorn and Wentzell 2011 ). I draw on relevant theories of masculinity, to show how masculinity is produced as both effeminophobic and hegemonic, as well as inclusive and neoliberal (Sedgwick 1991, Connell 1995, Anderson 2009, Hakim 2019 ). I continue to argue that masculinity emerges around three prevalent connection points in the marketing: anger, career and the masculine face . I discuss the generative and disciplining trajectories of these configurations and the possibilities of (un)becoming they entail for men, as they continue to engage with these emerging medical technologies of appearance enhancement.